Unlocking the secrets of saliva: the promising potential of salivary biomarkers for evaluating crack use - Marques, Sandra Silva; Oliveira, Taís Maria Cardoso; Zucco, Gabriela Ribeiro; Sabbag, Fernando; Martinho, Herculando da Silva; Almeida, Janete Dias; Araújo, Marcelo Ribeiro de (Brazilian Dental Science, 2023)
The forthcoming letter will encompass the following highlights: Crack cocaine use involves smoking a highly addictive form of cocaine, which is a significant concern in Brazil, particularly in urban areas. This addiction is linked to various health problems, including cardiovascular issues, sexually transmitted infections (STIs) like AIDS and syphilis, tuberculosis, and a notable increase in mortality, largely due to violent causes. Furthermore, crack cocaine users are particularly vulnerable to dental caries, gingival inflammation, oral mucosa lesions, and xerostomia KEYWORDS Crack Cocaine; Oral Health; Quality of Life; Body Fluids; Biomarkers.